Brain Reward & Stress Systems in Addiction - Nicholas W. Gilpin (Frontiers Research Topics, 2015)
Addiction to drugs and alcohol is a dynamic and multi-faceted disease process in humans, with devastating health and financial consequences for the individual and society-at-large. In humans, drug and alcohol use disorders (i.e., abuse and dependence) are defined by clusters of behavioral symptoms that can be modeled to various degrees in animals. Hallmark behavioral symptoms associated with drug and alcohol dependence are compulsive drug use, loss of control during episodes of drug use, the emergence of a negative emotional state in the absence of the drug, and chronic relapse vulnerability during drug abstinence. The transition to drug dependence is defined by neuroadaptations in brain circuits that, in the absence of drugs, mediate a variety of critical behavioral and physiological processes including natural reward, positive and negative emotional states, nociception, and feeding. Chronic drug exposure during the transition to dependence spurs (1) within-systems changes in neural circuits that contribute to the acute rewarding effects of the drug and (2) recruitment of brain stress systems (neuroendocrine and extra-hypothalamic). There are substantial genetic contributions to the propensity to use and abuse drugs, and drug abuse is highly co-morbid with various other psychiatric conditions (e.g., anxiety disorders, major depressive disorder) that may precede or follow the development of drug use problems. Across drugs of abuse, there are overlapping and dissociable aspects of the behavioral and neural changes that define the transition to dependence. Even within a single drug, people abuse drugs for a variety of reasons. The picture is further complicated by the fact that humans often abuse more than one drug concurrently. Even in the face of these challenges, pre-clinical and clinical research is making exponential gains into understanding the neurobiology of drug addiction. With the advent of new technologies and their combination with traditional approaches, the field is able to ask and answer addiction-related research questions in increasingly sophisticated ways. Here, we hope to assemble a collection of articles that provide an up-to-the-moment snapshot of the prevailing empirical, theoretical and technical directions in the addiction research field. We encourage submissions from all investigators working to understand the neurobiology of addiction, especially as it pertains to reward and stress pathways in the brain.